Utilization of Fermentation Process for the Production of Novel Plant-Based Meat Analogs: A Review of Microorganisms, Processing, and Regulations - Ozpinar, Fatma Beyza; Dere, Sevda; Altunay, Serdar; Sagdic, Osman; Dertli, Enes (WILEY, 2026)
The production of plant-based meat analogues from various protein sources is an emerging application worldwide, driven by growing population and health concerns. Many microorganisms during fermentation play a crucial role in fermented plant-based meat alternatives, together with structuring and analytical approaches in terms of nutritional, physicochemical, and textural properties. On the other hand, various countries enforce regulations and legislation for these products while producing and labeling them in order to protect consumers. This review focused on plant sources, microorganisms, and technologies applied to fermented meat alternatives, including 3D food printing, extrusion, and advanced biotechnological and analytical approaches such as precision fermentation, artificial intelligence, machine learning, and metabolomics analysis. Besides, dietary, chemical, flavor, and appearance effects were mentioned for these combinations. In addition, the review discusses legal regulations and labeling enforced in several countries, aimed at providing consumers with safe, healthy food by defining appropriate protein dosages. The techno-functional properties of plant-based meat alternatives improved owing to fermentation and microorganisms playing a vital role. This review also highlighted that other advanced technologies assisted in the development of better final products in line with consumer demands and legal regulations enforced to produce high-quality, safe, and healthy foods.
Keywords: fermentation; legal regulations; meat analogues; microorganisms; novel technologies; plant proteins; ALTERNATIVES; Food Science & Technology